PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP KEPUASAN KONSUMEN PADA KNTOR POS INDONESIA PEKANBARU - Resi Yulika; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the Indonesian Post Office in Pekanbaru. The problem in this research is the sale at the Pekanbaru Indonesia Post Office, the sales of which do not reach the targets set by the company, meaning there are problems with customer satisfaction. This was due to the fact that package delivery did not arrive on time and the level of competition was increasing. The purpose of this study was to determine the effect of service quality and corporate image on consumer satisfaction on the use of delivery services in the Indonesian post office Pekanbaru.Hypothesis testing is done by simple linear regression analysis and multiple linear regression analysis. The analysis shows that service quality and corporate image have an effect on increasing consumer satisfaction both partially and simultaneously. The results of the analysis show the coefficient of determination of 0.418 means that 41.8% change in the value of customer satisfaction is influenced by variables of service quality and corporate image while the remaining 58.2% is influenced by other variables not examined in this study.Keywords: Service Quality, Corporate Image, Consumer Satisfaction